Living pharmacy in urban yards: Health care in the Amazon - Lobato, Gerciene de Jesus Miranda; Lucas, Flávia Cristina Araújo; Gurgel, Ely Simone Cajueiro; Germano, Carolina Mesquita (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The ethnobotanical research group of in the Amazon in Universidade Estadual do Pará (Pará State University) has been studying the use of various plant species by traditional communities for the treatment and cure of diseases. This study aimed to identify the medicinal plants around the home most used in Bairro Mutirão, Abaetetuba, Pará, Brazil to correlate ethnopharmacological data with phytochemical studies, evaluating the contribution of these species to promote health in poor communities in the Amazon. There were non-participant observations, semi-structured interviews and guided tours in 189 yards. Phytochemical information was gathered from ScienceDirect, Scinfinder, Scopus, DataPlant, Hindawi Publishing Corporation. We identified 46 therapeutic species, particularly Aloe vera (L.) Burman. f.; Anacardium occidentale L.; Bixa orellana L.; Kalanchoe pinnata (Lam.) Pers.; Lippia alba (Mill.) N.E.Br. ex P. Wilson and, Morinda citrifolia L., noted in the scientific literature as having antitumor, soothing, anti-inflammatory and antimicrobial potential, confirming their ethnopharmacological use in home yards in Abaetetuba. The medicinal flora around homes in the Amazon is a path to the conservation of plant diversity in urbanized environments and potentially to the discovery of new drugs.